2016
DOI: 10.1038/srep35267
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin and resveratrol co-delivery nanoparticle to overcome doxorubicin resistance

Abstract: With the extensive application of doxorubicin (DOX), DOX resistance has become one of the main obstacles to the effective treatment of breast cancer. In this paper, DOX and resveratrol (RES) were co-encapsulated in a modified PLGA nanoparticle (NPS) to overcome the DOX resistance. CLSM results indicated that DOX and RES were simultaneously delivered into the nucleus of DOX-resistant human breast cancer cells by DOX/RES-loaded NPS. Consequently, DOX/RES-loaded NPS showed significant cytotoxicity on MDA-MB-231/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Pharmacokinetic analysis of amphiphilic compounds reveal predisposition of self-aggregation, that often leads to an undesirable initial burst-release, which was also the case in this study too, as drug particles, bound to the outer surface of the drug carrier, dissociate altogether (Fülöp et al 2013;Zhao et al 2016). Densely coating the microcarriers is realized as one way of reducing the burst release rate, though the proportion of SPA incorporation in the microcarriers would become much more restricted (Suk and Xu 2017).…”
Section: Doxorubicin Release Studysupporting
confidence: 62%
“…Pharmacokinetic analysis of amphiphilic compounds reveal predisposition of self-aggregation, that often leads to an undesirable initial burst-release, which was also the case in this study too, as drug particles, bound to the outer surface of the drug carrier, dissociate altogether (Fülöp et al 2013;Zhao et al 2016). Densely coating the microcarriers is realized as one way of reducing the burst release rate, though the proportion of SPA incorporation in the microcarriers would become much more restricted (Suk and Xu 2017).…”
Section: Doxorubicin Release Studysupporting
confidence: 62%
“…This could be interpreted as enhancing the bioavailability of RSV by nanoformulation. Similarly, Zhao et al [15] stated that Dox and RSV co-encapsulated in modified PLGA NPs significantly inhibited Dox-resistant tumor growth in MDA-MB-231 and MCF-7 tumor-bearing mice without causing significant systemic toxicity. Moreover, RSV nanocomposite had a high anticancer efficacy against mouse colon cancer cells CT26 in vitro and in a xenograft mouse model with less tissue toxicity [35].…”
Section: Discussionmentioning
confidence: 94%
“…Generally, we recommend using NP-RSV as a therapeutic to control colon cancer.Numerous studies have showed an enhancement in the bioavailability of RSV by nanoformulations and an increase in the sensitivity of cancer cells to chemotherapy. Zhao et al [15] found an increase in the sensitivity of breast cancer-bearing mice to co-delivery of doxorubicin (Dox) and RSV via poly glyco-lactic acid (PLGA) nanoparticles (NPs) to overcome Dox resistance. Moreover, RSV oral bioavailability was increased 10 times when loaded in casein NPs [16].…”
mentioning
confidence: 99%
“…Free DOX accumulates in the nucleus because the molecules enter cells via the free diffusion pathway, and are quickly transferred to the nucleus, where they strongly bind to chromosomal DNA. 31,32 In contrast, DOX-loaded NPs are taken up via endocytosis and accumulate in the lysosomes, where the nanocarriers degrade and drug release occurs. 33 Overall, DOX-SPIO cellular uptake efficiency was significantly improved by surface modification with MSC membranes.…”
Section: Internalization By Mc38 Cellsmentioning
confidence: 99%